Simulation Technique of Synchronous Reluctance Bearingless Machine (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Magnetically levitated rotor electric machines can be used under such conditions wherein application of conventional bearings is impossible because of presence of lubrication. Active magnetic bearings application requires rotor length increase and stalling speed is decreased. Bearingless electric machines are the next step up of the magnetically levitated rotor machines. A bearingless electric machine module generates electromagnetic torque and radial forces. This feature makes possible to decrease the rotor length on retention of capacity of torque and forces. It is necessary to verify a control system operation algorithm via simulation model owing to complexity of machine electromagnetic interaction. It is practical to use a variable attribute set model for this purpose. The following article considers one of these models for researching the system via MATLAB Simulink. Basic relations for programmatic model creation are presented. Comparative assessment of various machine model types is made.